2014
DOI: 10.1136/heartasia-2013-010431
|View full text |Cite
|
Sign up to set email alerts
|

A case control study on autopsy findings in sudden unexplained nocturnal death syndrome

Abstract: Aim Sudden unexplained nocturnal death syndrome (SUNDS) has been linked to the Brugada syndrome. In some places, acute haemorrhagic pancreatitis is widely held to cause it. We conducted a systematic, controlled autopsy study on Filipino SUNDS victims to rule out structural heart findings as well as acute haemorrhagic pancreatitis as causes. Methods and results A case control autopsy study was conducted comparing SUNDS victims between 18 and 50 years of age who died within 1 h of symptom onset with age-and gend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
5
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 31 publications
3
5
2
Order By: Relevance
“…The finding is also in contrast to a study performed by Gervacio et al. who found that only one of 24 (4.2%) Filipino SUNDS cases had coronary atherosclerosis. Such previous findings suggest that coronary atherosclerosis found in Thai SUNDS cases might be coincident without pathologic signs of either recent or old myocardial infarction.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The finding is also in contrast to a study performed by Gervacio et al. who found that only one of 24 (4.2%) Filipino SUNDS cases had coronary atherosclerosis. Such previous findings suggest that coronary atherosclerosis found in Thai SUNDS cases might be coincident without pathologic signs of either recent or old myocardial infarction.…”
Section: Discussioncontrasting
confidence: 99%
“…Most SUNDS cases in this study were located in the Northeastern region of Thailand, which is consistent with previous Thai studies . All SUNDS cases in this study only occurred in young or middle‐aged men, being consistent with previous Thai studies but not in other ethnic studies , which reported that men were 3.9–13.9 times more affected than women. Most SUNDS cases in this study were blue‐collar construction workers, who migrated from their original birth region to Bangkok for labor.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…3 Previous study showed that mild respiratory tract infection or exposure to cigarette smoke may be the factors associated with these deaths 10 and that acute hemorrhagic pancreatitis, hemorrhagic congestion, edema of the lungs, infection with Pseudomonas pseudomallei, or cardiac conduction system abnormalities may explain the death of very rare SUNDS victims. 11,12 So far, there is no fatal pathological changes found in the vast majority of SUNDS decedents. 13 Brugada syndrome was reported to be phenotypically, genetically, and functionally the same disorder with SUNDS based on 3 pathogenic SCN5A mutations found in SUNDS cases.…”
mentioning
confidence: 98%
“…6 Kampuchea, Laos, and Hmong refugees in the United States were also reported to have a high incidence (59, 82, and 92 per 100,000 people years, respectively) of SUNDS. 7,8 The annual incidence of SUNDS is approximately 1–3 per 100,000 people in Southern China. 4,9 …”
mentioning
confidence: 99%